2016
DOI: 10.1002/qj.2953
|View full text |Cite
|
Sign up to set email alerts
|

Sea‐surface emissivity parametrization from microwaves to millimetre waves

Abstract: In preparation for new observations on board the next generation of the European operational meteorological satellite (EUMETSAT Polar System -Second Generation(EPS-SG)), a parametrization of the sea-surface emissivity is proposed from 10-700 GHz: Tool to Estimate Sea-Surface Emissivity from Microwaves to sub-Millimeter waves (TESSEM 2 ). It is based on the community model FAST microwave Emissivity Model (FASTEM) at frequencies up to 200 GHz, where FASTEM has been calibrated and validated operationally. It foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…The proposed methodology involves a series of coupling tools. The Tool to Estimate Land Surface Emissivities from Microwave to Sub-millimeter waves (TELSEM2; Wang et al, 2016) and the Tool to Estimate Sea Surface Emissivity from Microwave to Sub-millimeter waves (TESSEM2; Prigent et al, 2016) are used to determine land and ocean surface emissivities respectively. TELSEM2 provides the emissivity (V and H components) for any location, month and incidence angle with a spatial resolution of 0.25 • .…”
Section: The Radiative Transfer Model: Artsmentioning
confidence: 99%
“…The proposed methodology involves a series of coupling tools. The Tool to Estimate Land Surface Emissivities from Microwave to Sub-millimeter waves (TELSEM2; Wang et al, 2016) and the Tool to Estimate Sea Surface Emissivity from Microwave to Sub-millimeter waves (TESSEM2; Prigent et al, 2016) are used to determine land and ocean surface emissivities respectively. TELSEM2 provides the emissivity (V and H components) for any location, month and incidence angle with a spatial resolution of 0.25 • .…”
Section: The Radiative Transfer Model: Artsmentioning
confidence: 99%
“…In that direction, the recently developed parameterization of sea surface emissivity generated by the Tool to Estimate Sea Surface Emissivity from Microwave to sub-Millimeter waves (TESSEM2) [85] was selected. Moreover, lambertian reflection was assumed.…”
Section: Radiative Transfer Simulationsmentioning
confidence: 99%
“…Liu et al (2011) tested FASTEM up to 150 GHz. Prigent et al (2016) compared FASTEM with the Tool to Estimate Sea-Surface Emissivity from Microwaves to sub-Millimeter waves (TESSEM2) and with ISMAR measurements from two low-level flights at low wind speeds. They showed that FASTEM tends to underestimate the emissivity at 243.3 GHz leading to errors of order 5 K in the upwelling brightness temperature close to the surface (flight altitudes < 300 m).…”
Section: Radiative Transfer Simulationsmentioning
confidence: 99%